Anti-picking finishing method for micro-porous polyester fiber fabric

CN122980221APending Publication Date: 2026-10-27DONGTAI JIRUI TEXTILE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611408498.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]为了解决因相关的微孔涤纶纤维采用湿法表面成膜整理而导致难以兼顾耐用性与功能性的问题,本申请提供一种微孔涤纶纤维面料的防勾丝后整理方法

Benefits of technology

1、由于本申请采用可升华占位剂预填充微孔再进行表面成膜与升华释孔的组合方法,利用固态占位剂对微孔的封堵使成膜整理液停留在纤维外表面,再通过固-气相变无残留地恢复微孔结构,避免湿法整理堵塞功能孔道的矛盾,因此获得防勾丝性能与微孔涤纶透湿、透气与导湿功能兼具的面料,且薄膜连续致密,耐久性高的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980221A_ABST
    Figure CN122980221A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of textiles, and particularly discloses a post-treatment method for preventing hooking of micro-porous polyester fiber fabric. The method comprises the following steps: S1, immersing the micro-porous polyester fiber fabric in a solution to obtain an immersed fabric; S2, drying the immersed fabric to obtain a space-occupying and filling fabric; S3, immersing and padding the space-occupying and filling fabric with a finishing liquid to obtain fabric covered with the finishing liquid; S4, drying and curing the fabric covered with the finishing liquid to obtain a film-forming fabric; S5, exposing the film-forming fabric to steam of a gas-phase silane coupling agent for treatment to obtain an interface-modified fabric; S6, heating the interface-modified fabric to obtain a pore-releasing fabric; and S7, cooling the pore-releasing fabric to obtain the micro-porous polyester fiber fabric subjected to the post-treatment method for preventing hooking. The post-treatment method for preventing hooking can be used for micro-porous polyester sports and outdoor functional fabric, and has the advantages of preventing hooking and the wet permeability, air permeability and moisture conduction of the micro-porous polyester.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of solid waste treatment and resource utilization technology, and more specifically, it relates to an anti-snagging finishing method for microporous polyester fiber fabric. Background Technology

[0002] Microporous polyester fiber fabrics, with their unique microporous structure, are widely used in sports and outdoor functional clothing. Their excellent moisture permeability, breathability, and moisture wicking properties can effectively improve wearing comfort. To solve the problem of polyester fabrics being prone to snagging, the industry generally adopts surface film-forming finishing technology, which enhances anti-snagging ability by coating the fiber surface with a polymer film. This method is simple, cost-controllable, and can significantly improve the surface abrasion resistance and anti-snagging level of the fabric. Conventional surface film-forming methods can improve the anti-snagging level and meet basic durability requirements.

[0003] The relevant microporous polyester fibers are treated with conventional wet surface film forming to construct a protective polymer film on the fiber surface to improve anti-snagging and abrasion resistance. However, during the film forming process, the liquid finishing liquid is easily wetted and penetrated into the microporous channels inside the fiber under the action of capillary effect. As a result, the microporous structure that gives the fabric its functionality is non-selectively covered and blocked by the polymer, which causes the original core properties of the fabric, such as moisture permeability, breathability and moisture wicking, to decrease after film forming, making it difficult to balance durability and functionality. Summary of the Invention

[0004] To address the issue of difficulty in balancing durability and functionality caused by wet surface film formation finishing of microporous polyester fibers, this application provides an anti-snagging finishing method for microporous polyester fiber fabrics.

[0005] This application provides a method for preventing snags in microporous polyester fiber fabrics, using the following technical solution: A method for preventing snagging on microporous polyester fiber fabric, comprising the following steps: S1. The microporous polyester fiber fabric is immersed in a solution containing a sublimable organic small molecule spacer to obtain the impregnated fabric. S2. Dry the impregnated fabric to allow the solvent to evaporate and the placer to crystallize and precipitate in the micropores, thereby obtaining a placer filling fabric. S3. The filling fabric is impregnated with a finishing liquid containing a film-forming polymer and a crosslinking agent to obtain a fabric coated with the finishing liquid. S4. The fabric coated with finishing liquid is dried and cured to form an anti-snagging polymer film on the outer surface of the fibers, thus obtaining a film-forming fabric. S5. The film-forming fabric is exposed to the vapor of a gaseous silane coupling agent for treatment, and a sacrificial layer is generated in situ at the interface between the placer and the anti-snagging film to obtain an interface-modified fabric. S6. The interface-modified fabric is subjected to heat treatment to sublimate the placer and allow it to escape from the micropores, thereby obtaining a pore-releasing fabric. S7. Cool the porous fabric to obtain a microporous polyester fiber fabric with anti-snagging finishing.

[0006] By adopting the above technical solution, the micropores of the microporous polyester fabric are first pre-filled and sealed with a sublimable placer to form a physical protective template, so that the film-forming finishing liquid applied later only stays on the outer surface of the fiber and cannot penetrate into the pores. After a continuous anti-snagging film is formed on the fiber surface, a nanoscale sacrificial release layer is constructed at the interface between the placer and the film by treating with a gas-phase silane coupling agent. Then, the placer is sublimated and escaped by dry heating, completely restoring the original structure of the micropores. At the same time, the placer leaves micro-pits after sublimation at the pre-set eutectic points in the amorphous region of the fiber, which promotes the filling of film molecular chain segments to form mechanical anchoring. The whole process avoids the blockage of micropores by liquid media and the damage to the film by washing. The resulting fabric has durable anti-snagging ability while fully retaining the inherent moisture permeability, air permeability and moisture wicking function of microporous polyester. The film has excellent adhesion and the fabric has a soft and natural feel.

[0007] Preferably, in step S1, the sublimable organic small molecule occupier is selected from at least one of menthol, camphor, naphthalene, or benzophenone alkyl-substituted derivatives.

[0008] By adopting the above technical solution, the selected substances are all small organic molecules with a clear sublimation temperature and chemical inertness to polyester. They can fully penetrate into the micropores through capillary action and tightly fill the pores in a crystalline state after the solvent evaporates. These placers directly transform from solid to gas phase under subsequent heating conditions, leaving no liquid phase residue. This ensures the reliability of filling and sealing, and achieves traceless removal without causing swelling or stress damage to the anti-snagging film and fiber matrix, thus ensuring the restoration of functional micropores.

[0009] Preferably, the alkyl-substituted benzophenone derivative is 4-methylbenzophenone or 4,4'-dimethylbenzophenone.

[0010] By adopting the above technical solution, there is a specific intermolecular interaction between this type of benzophenone derivative and the amorphous region of polyester fiber. During the controlled crystallization process, it can induce the micro-order rearrangement of the molecular chain segments on the fiber surface and form nanoscale eutectic embedding points. These eutectic points become sacrificial pore-forming templates in the subsequent sublimation step, leaving micro-pits in situ that match the size of the polymer chain of the anti-snagging film. This provides a structural basis for achieving in-situ anchoring of the film and enhances the bonding strength between the anti-snagging layer and the fiber.

[0011] Preferably, in step S1, the solution is an ethanol solution of a spacer, and the mass concentration of the spacer is 5% to 30%.

[0012] By adopting the above technical solution, ethanol is used as a solvent to quickly wet and penetrate the multi-level pores of microporous polyester, and evaporates rapidly under mild and dry conditions, causing the placer to fill the micropores evenly as fine crystals. By controlling the mass concentration of the placer within the above range, it is ensured that the amount of crystallization is sufficient to completely seal the micropores, while avoiding excessive placer residue in the fiber gaps or on the surface to form a thick layer. This ensures that the subsequent finishing solution forms a film only on the outermost layer of the fiber, making the interface between the anti-snagging film and the fiber matrix clear.

[0013] Preferably, in step S2, the drying includes: first removing the solvent at 40~60°C, and then cooling to -5~10°C at a cooling rate of 0.5~5°C / min, so that the placer forms nanoscale eutectic embedding points on the surface of the amorphous region of the polyester fiber.

[0014] By adopting the above technical solution, the segmented temperature-controlled drying process allows the placer to undergo a slow cooling process from a higher temperature to a lower temperature after the solvent escapes. This provides sufficient thermodynamic driving force and time window for the orderly arrangement of placer molecules in the amorphous region of polyester. The specific cooling rate and final temperature range are conducive to inducing the placer and fiber polymer chains to form uniformly distributed eutectic points, without causing phase separation or coarse crystallization due to rapid cooling. This provides precise conditions for the formation of the in-situ anchoring structure after subsequent sublimation.

[0015] Preferably, in step S3, the film-forming polymer is an aqueous polyurethane or polyacrylate, and the crosslinking agent is a blocked isocyanate crosslinking agent; the concentration of the film-forming polymer in the finishing solution is 20-80 g / L, and the amount of crosslinking agent is 2%-8% of the mass of the film-forming polymer.

[0016] By adopting the above technical solution, waterborne polyurethane or polyacrylate forms a continuous film with excellent flexibility and abrasion resistance on the fiber surface. The blocked isocyanate crosslinking agent is unblocked at the curing temperature and participates in the crosslinking reaction, so that the film forms a three-dimensional network structure, which greatly improves its cohesive strength and water washability. The reasonable matching of the film-forming polymer concentration and the amount of crosslinking agent allows the finishing liquid to spread and form a uniform and defect-free coating layer during padding, while avoiding excessive thickening that would cause stiffness or additional reduction in air permeability.

[0017] Preferably, in step S4, the drying temperature is 60~90℃ and the time is 2~10min; the curing temperature is 120~150℃ and the time is 1~5min.

[0018] By adopting the above technical solution, the moisture is first removed by drying at a lower temperature, which allows the polymer particles to agglomerate uniformly and form a preliminary film, avoiding the formation of a skin on the surface and the retention of internal moisture due to instantaneous high temperature. Then, the film is cured at a higher temperature, which promotes the full desealing of the crosslinking agent and its reaction with the active groups on the polymer chain to form a dense crosslinked structure. This step-by-step heat treatment process optimizes the density, mechanical strength and adhesion to fibers of the anti-snagging film, while avoiding thermal damage to the microporous structure that has been occupied and protected.

[0019] Preferably, in step S5, the gas-phase silane coupling agent is hexamethyldisilazane or trimethylchlorosilane, the treatment temperature is 25~60℃, and the treatment time is 10~40min.

[0020] By adopting the above technical solution, a silane coupling agent is introduced in gas phase. Its molecules diffuse along the free volume voids of the film and the microchannels of the fiber end face to the interface between the placer and the anti-snagging film, and selectively undergo hydrolysis condensation or physical adsorption at the interface to form a nanoscale release layer rich in methyl groups. This sacrificial layer acts as a solid separation medium in the subsequent sublimation process, effectively blocking the direct contact and friction between the placer crystals and the inner wall of the film, eliminating micro-tears or interface weakening caused by crystal peeling, thereby preserving the integrity of the anti-snagging film.

[0021] Preferably, in step S6, the heating treatment temperature is 80~105℃ and the time is 15~60min.

[0022] By adopting the above technical solution, the temperature is set above the sublimation temperature of the placer and far below the softening point of the polyester fiber, driving the placer to directly transform from solid to gas at a constant rate and diffuse out, while maintaining the dimensional stability of the polyester fiber and the anti-snagging film. During the continuous escape of the placer, the micro-pits formed at the eutectic points on the fiber surface are gradually filled by the polymer chain segments of the anti-snagging film due to local thermal motion, forming a firm mechanical rivet. Thus, while the micropores are completely restored, the film anchoring and strengthening are achieved, significantly improving the wash resistance and abrasion resistance durability of the anti-snagging effect.

[0023] Preferably, step S6 further includes condensing and recovering the sublimated spacer vapor to obtain a recovered spacer, which is then reused to prepare the solution from step S1.

[0024] By adopting the above technical solution, the vapor of the placer released during the sublimation process is captured and recovered by condensation, avoiding its direct emission into the environment. At the same time, the recovered placer has high purity and can be directly recycled for the preparation of the pretreatment impregnation solution. This closed-loop recovery method reduces the consumption of raw materials in long-term production, makes the overall process meet the requirements of green manufacturing, and will not have any adverse effects on the quality of the fabric.

[0025] In summary, this application has the following beneficial effects: 1. Because this application uses a combination of pre-filling micropores with a sublimable placer and then performing surface film formation and sublimation to release pores, the solid placer blocks the micropores, allowing the film-forming finishing liquid to remain on the outer surface of the fiber. Then, the micropore structure is restored without residue through solid-gas phase change, avoiding the contradiction of wet finishing blocking functional channels. Therefore, a fabric with anti-snagging performance and the moisture permeability, breathability and moisture wicking function of microporous polyester is obtained, and the film is continuous, dense and durable.

[0026] 2. In this application, benzophenone alkyl-substituted derivatives are preferably used as site-filling agents and the crystallization cooling rate is controlled. Since such substances can form nanoscale eutectic embedding points with the amorphous region of polyester, a sacrificial template is pre-placed during the controlled crystallization process. After sublimation, micro-pits are left in situ for the molecular chain segments of the anti-snagging film to fill in, forming a mechanical anchoring structure. Therefore, the adhesion of the anti-snagging film to the fiber surface is further enhanced, and the wash resistance and abrasion resistance are improved.

[0027] 3. The method of this application introduces a gaseous silane coupling agent after film formation and before sublimation to generate a nanoscale sacrificial release layer at the interface between the placer crystal and the anti-snagging film. This ensures that there is no direct friction between the placer and the film during sublimation, thus ensuring the integrity of the anti-snagging film, avoiding performance degradation caused by micro-damage to the film layer, and maintaining the film's excellent flexibility and density.

[0028] 4. The method of this application achieves closed-loop recycling of the spacer by condensing and recovering the sublimated spacer vapor and reusing it to prepare the spacer solution, thereby reducing raw material consumption, making the overall process meet environmental protection requirements, and the purity and performance of the recovered spacer do not affect the finishing effect. Attached Figure Description

[0029] Figure 1 This is a flowchart illustrating an anti-snagging finishing method for microporous polyester fiber fabric proposed in this application. Detailed Implementation

[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.

[0031] Technical concept: The relevant microporous polyester fibers are treated with conventional wet surface film forming to construct a protective polymer film on the fiber surface to improve anti-snagging and abrasion resistance. However, during the film forming process, the liquid finishing liquid is easily wetted and penetrated into the microporous channels inside the fiber under the action of capillary effect. As a result, the microporous structure that gives the fabric its functionality is non-selectively covered and blocked by the polymer, which causes the original core properties of the fabric, such as moisture permeability, breathability and moisture wicking, to decrease after film forming, making it difficult to balance durability and functionality.

[0032] This application discloses a method for anti-snagging finishing of microporous polyester fiber fabric. The method includes the following steps: S1, immersing the microporous polyester fiber fabric in a solution to obtain an impregnated fabric; S2, drying the impregnated fabric to obtain a filler fabric; S3, padding the filler fabric with a finishing solution to obtain a fabric coated with the finishing solution; S4, drying and curing the fabric coated with the finishing solution to obtain a film-forming fabric; S5, exposing the film-forming fabric to vapors of a fumed silane coupling agent to obtain an interface-modified fabric; S6, heating the interface-modified fabric to obtain a pore-release fabric; S7, cooling the pore-release fabric to obtain the anti-snagging microporous polyester fiber fabric.

[0033] This application employs a combination of pre-filling micropores with a sublimable placeholder agent followed by surface film formation and sublimation-release method. By using a solid placeholder agent to seal the micropores, the film-forming finishing liquid remains on the outer surface of the fiber. Then, through a solid-gas phase change, the microporous structure is restored without residue, avoiding the contradiction of wet finishing blocking functional channels. Therefore, a fabric that combines anti-snagging performance with the inherent moisture permeability, air permeability, and moisture wicking function of microporous polyester is obtained, and the film is continuous, dense, and highly durable.

[0034] Example 1: This example provides a method for anti-snagging finishing of microporous polyester fiber fabric, comprising the following steps: S1. The microporous polyester fiber fabric is immersed in a solution containing a sublimable organic small molecule spacer to obtain the impregnated fabric. Among them, the sublimable organic small molecule occupier is menthol.

[0035] The solution is an ethanol solution of the site-occupying agent, and the mass concentration of the site-occupying agent is 5%.

[0036] S2. Dry the impregnated fabric to allow the solvent to evaporate and the placer to crystallize and precipitate in the micropores, thus obtaining the placer filling fabric. The drying process includes: first, removing the solvent at 40°C, and then cooling to -5°C at a cooling rate of 0.5°C / min, so that the placer forms nanoscale eutectic embedding points on the surface of the amorphous region of the polyester fiber.

[0037] S3. Impregnate the filling fabric with a finishing solution containing a film-forming polymer and a crosslinking agent to obtain a fabric coated with the finishing solution. The film-forming polymer is waterborne polyurethane or polyacrylate, and the crosslinking agent is a blocked isocyanate crosslinking agent; the concentration of the film-forming polymer in the finishing solution is 20 g / L, and the amount of crosslinking agent is 2% of the mass of the film-forming polymer.

[0038] S4. The fabric coated with finishing liquid is dried and cured to form an anti-snagging polymer film on the outer surface of the fibers, thus obtaining a film-forming fabric. The drying temperature is 60℃ and the time is 2 minutes; the curing temperature is 120℃ and the time is 1 minute.

[0039] S5. The film-forming fabric is exposed to the vapor of the gaseous silane coupling agent for treatment, and a sacrificial layer is generated in situ at the interface between the spacer and the anti-snagging film to obtain the interface-modified fabric. The gas-phase silane coupling agent is hexamethyldisilazane or trimethylchlorosilane, the treatment temperature is 25℃, and the treatment time is 10 min.

[0040] S6. Heat the interface-modified fabric to sublimate the spacer and allow it to escape from the micropores, thus obtaining a release-pore fabric. The heating treatment was carried out at a temperature of 80℃ for 15 minutes.

[0041] This also includes condensing and recovering the sublimated spacer vapor to obtain recovered spacer, which is then reused in the preparation of the solution in step S1.

[0042] S7, Cooling and releasing the porous fabric, which is a microporous polyester fiber fabric with anti-snagging finishing.

[0043] Example 2: This example provides a method for anti-snagging finishing of microporous polyester fiber fabric, comprising the following steps: S1. The microporous polyester fiber fabric is immersed in a solution containing a sublimable organic small molecule spacer to obtain the impregnated fabric. Among them, the sublimable organic small molecule occupiers are camphor or naphthalene.

[0044] The solution is an ethanol solution of the site-occupying agent, and the mass concentration of the site-occupying agent is 30%.

[0045] S2. Dry the impregnated fabric to allow the solvent to evaporate and the placer to crystallize and precipitate in the micropores, thus obtaining the placer filling fabric. The drying process includes: first, removing the solvent at 60°C, and then cooling to 10°C at a cooling rate of 5°C / min, so that the placer forms nanoscale eutectic embedding points on the surface of the amorphous region of the polyester fiber.

[0046] S3. Impregnate the filling fabric with a finishing solution containing a film-forming polymer and a crosslinking agent to obtain a fabric coated with the finishing solution. The film-forming polymer is waterborne polyurethane or polyacrylate, and the crosslinking agent is a blocked isocyanate crosslinking agent; the concentration of the film-forming polymer in the finishing solution is 80 g / L, and the amount of crosslinking agent is 8% of the mass of the film-forming polymer.

[0047] S4. The fabric coated with finishing liquid is dried and cured to form an anti-snagging polymer film on the outer surface of the fibers, thus obtaining a film-forming fabric. The drying temperature is 90℃ and the time is 10 minutes; the curing temperature is 150℃ and the time is 5 minutes.

[0048] S5. The film-forming fabric is exposed to the vapor of the gaseous silane coupling agent for treatment, and a sacrificial layer is generated in situ at the interface between the spacer and the anti-snagging film to obtain the interface-modified fabric. The gas-phase silane coupling agent is hexamethyldisilazane or trimethylchlorosilane, the treatment temperature is 60℃, and the treatment time is 40 min.

[0049] S6. Heat the interface-modified fabric to sublimate the spacer and allow it to escape from the micropores, thus obtaining a release-pore fabric. The heating treatment was carried out at a temperature of 105℃ for 60 minutes.

[0050] This also includes condensing and recovering the sublimated spacer vapor to obtain recovered spacer, which is then reused in the preparation of the solution in step S1.

[0051] S7, Cooling and releasing the porous fabric, which is a microporous polyester fiber fabric with anti-snagging finishing.

[0052] Example 3: This example provides a method for anti-snagging finishing of microporous polyester fiber fabric, comprising the following steps: S1. The microporous polyester fiber fabric is immersed in a solution containing a sublimable organic small molecule spacer to obtain the impregnated fabric. Among them, the sublimable organic small molecule site occupier is a benzophenone alkyl-substituted derivative.

[0053] Among them, the alkyl-substituted derivatives of benzophenone are 4-methylbenzophenone or 4,4'-dimethylbenzophenone.

[0054] The solution is an ethanol solution of the site-occupying agent, and the mass concentration of the site-occupying agent is 17.5%.

[0055] S2. Dry the impregnated fabric to allow the solvent to evaporate and the placer to crystallize and precipitate in the micropores, thus obtaining the placer filling fabric. The drying process includes: first, removing the solvent at 50°C, and then cooling to 2.5°C at a cooling rate of 2.75°C / min, so that the placer forms nanoscale eutectic embedding points on the surface of the amorphous region of the polyester fiber.

[0056] S3. Impregnate the filling fabric with a finishing solution containing a film-forming polymer and a crosslinking agent to obtain a fabric coated with the finishing solution. The film-forming polymer is waterborne polyurethane or polyacrylate, and the crosslinking agent is a blocked isocyanate crosslinking agent; the concentration of the film-forming polymer in the finishing solution is 50 g / L, and the amount of crosslinking agent is 5% of the mass of the film-forming polymer.

[0057] S4. The fabric coated with finishing liquid is dried and cured to form an anti-snagging polymer film on the outer surface of the fibers, thus obtaining a film-forming fabric. The drying temperature is 75℃ and the time is 6 minutes; the curing temperature is 135℃ and the time is 3 minutes.

[0058] S5. The film-forming fabric is exposed to the vapor of the gaseous silane coupling agent for treatment, and a sacrificial layer is generated in situ at the interface between the spacer and the anti-snagging film to obtain the interface-modified fabric. The gas-phase silane coupling agent is hexamethyldisilazane or trimethylchlorosilane, the treatment temperature is 42.5℃, and the treatment time is 25 min.

[0059] S6. Heat the interface-modified fabric to sublimate the spacer and allow it to escape from the micropores, thus obtaining a release-pore fabric. The heating treatment was carried out at a temperature of 92.5℃ for 37.5 minutes.

[0060] This also includes condensing and recovering the sublimated spacer vapor to obtain recovered spacer, which is then reused in the preparation of the solution in step S1.

[0061] S7, Cooling and releasing the porous fabric, which is a microporous polyester fiber fabric with anti-snagging finishing.

[0062] Comparative Example 1: This comparative example refers to the content of Example 1, except that the mass concentration of the placer in step S1 is 2%, and the rest is the same as Example 1.

[0063] Comparative Example 2: This comparative example refers to the content of Example 1, except that the cooling rate of drying in step S2 is 8°C / min and the final cooling temperature is 15°C. The rest of the content is the same as that of Example 1.

[0064] Comparative Example 3: This comparative example is the same as that in Example 1, except that the concentration of the film-forming polymer in the finishing solution in step S3 is 10 g / L. The rest of the contents are the same as those in Example 1.

[0065] Comparative Example 4: This comparative example refers to the content of Example 1, except that the curing temperature in step S4 is 170°C, and the rest is the same as Example 1.

[0066] Comparative Example 5: This comparative example refers to the content of Example 1, except that the treatment time of the gas phase silane coupling agent in step S5 is 5 minutes, and the rest is the same as Example 1.

[0067] Comparative Example 6: This comparative example refers to the content of Example 1, except that the heating temperature in step S6 is 70°C, and the rest is the same as Example 1.

[0068] Performance testing Sample preparation: Microporous polyester fiber fabric from the same batch was selected as the substrate and subjected to anti-snagging finishing according to the methods described in the examples and comparative examples to obtain finished fabric samples; another piece of microporous polyester fiber fabric from the same batch without any anti-snagging finishing was taken as a blank control sample, and another piece of microporous polyester fiber fabric from the same batch treated with conventional surface film forming method was taken as a conventional control sample. The conventional surface film forming method is to perform only pad-on film forming finishing solution and drying curing treatment without filling and sublimation pore release process; all samples were conditioned to humidity equilibrium under standard atmospheric conditions and then their performance was tested.

[0069] Anti-snagging performance testing: The anti-snagging level of the examples, comparative examples, blank control samples, and conventional control samples was evaluated according to the national standard GB / T11047 "Evaluation of Snagging Performance of Textile Fabrics - Hammer Method". During the test, each sample was cut into specimens of the specified size and mounted on a hammer-type anti-snagging tester, with the hammer continuously rotating a specified number of times on the specimen surface at a specified speed. After the test, the specimens were removed and visually rated under standard evaluation conditions, comparing them to standard photographs. The anti-snagging level is expressed as a grade; a higher grade indicates better anti-snagging performance.

[0070] Moisture permeability testing: Moisture permeability testing was conducted on the examples, comparative examples, blank control samples, and conventional control samples according to the national standard GB / T12704.1 "Textiles - Test Methods for Moisture Permeability of Fabrics - Part 1: Moisture Absorption Method". Each sample was placed over a moisture permeation cup containing a measured amount of desiccant, sealed, and then placed in a constant temperature and humidity test chamber at the specified temperature and relative humidity. After specified time intervals, the moisture permeation cup was removed, and the mass increment of the desiccant was measured. The moisture permeability of the fabric was calculated based on the mass increment, effective test area, and test time.

[0071] Air permeability test: The air permeability of the examples, comparative examples, blank control samples and conventional control samples were tested in accordance with the national standard GB / T5453 "Determination of air permeability of textile fabrics". Each sample was clamped on the test head round table of the air permeability meter in sequence, and the air flow rate through the unit area of ​​the fabric was measured under the specified pressure difference condition. The air permeability value of each sample was recorded.

[0072] Vapor wicking height test: The moisture wicking performance of the examples, comparative examples, blank control samples and conventional control samples was tested in accordance with the industry standard FZ / T01071 "Test Method for Capillary Effect of Textiles". Each sample was cut into strips of fabric of a specified width. Under standard atmospheric conditions, one end of the sample was suspended vertically and its lower end was immersed in a liquid tank containing distilled water. After a specified time, the height of the liquid surface where the water rose along the fabric was measured and the wicking height value was recorded to evaluate the moisture wicking ability of the fabric.

[0073] Anti-snagging performance testing after washing: According to the standard washing procedure in the national standard GB / T8629 "Home washing and drying procedures for testing textiles", the examples, comparative examples, and conventional control samples were subjected to multiple home washing cycles. After washing, the samples were dried and conditioned to humidity equilibrium under standard atmospheric conditions. Then, the anti-snagging level of each sample after washing was determined again according to the hammer test method described in the national standard GB / T11047. The change in the anti-snagging level before and after washing was compared to evaluate the adhesion and durability of the anti-snagging film.

[0074] Abrasion resistance testing: According to the abrasion test method specified in the national standard GB / T3920 "Textiles - Tests for color fastness - Color fastness to rubbing", the examples, comparative examples, and conventional control samples were subjected to dry and wet abrasion resistance tests. Each sample was fixed on the platform of the abrasion tester, and a friction head of a specified mass was wrapped with a standard abrasion cloth and moved back and forth on the sample surface at a specified stroke and number of times. After the test, the surface of the anti-snagging film was visually evaluated for wear, peeling, or damage, and the abrasion resistance integrity of the film was rated according to the grade.

[0075] Finishing agent residue and wastewater discharge detection: For the spacer vapor condensation and recovery process used in step S6 of the example, the condensate was collected, and the purity of the spacer was analyzed by gas chromatography. Simultaneously, the total amount of wastewater and the chemical oxygen demand (COD) of the wastewater generated during each batch of finishing was recorded. A comparative example and a conventional operation without condensation recovery were used as comparisons. The wastewater discharge per kilogram of fabric during finishing and the residual concentration of the spacer in the wastewater were measured to evaluate the green and environmentally friendly characteristics of the process. The COD of the wastewater was tested according to the national standard GB / T11914 "Determination of Chemical Oxygen Demand in Water - Dichromate Method".

[0076] Table 1: Test Results of Anti-snagging Performance and Moisture Permeability, Air Permeability and Moisture Traction Performance

[0077] Table 2: Test results of anti-snagging and abrasion resistance after washing

[0078] Table 3: Results of Finishing Agent Residue and Wastewater Discharge Tests

[0079] Example Conclusion: As can be seen from Examples 1-3 and Comparative Example 1, and Table 1, when the mass concentration of the placer in step S1 is lower than the protection range of this application, the amount of placer crystals is insufficient to completely fill and seal the various levels of pores in the microporous polyester. This results in the subsequent film-forming finishing liquid partially penetrating into the micropores and, after solidification, blocking some functional pores, causing a decrease in the fabric's moisture permeability, air permeability, and wicking height. At the same time, because the micropores are not adequately protected, the continuity of the anti-snagging film formed on the fiber surface is damaged, and the anti-snagging level is also reduced. The examples control the placer concentration within the protection range, and the solid placer forms a physical protection in the micropores, isolating the finishing liquid from contact with the inner wall of the pores. This not only gives the fabric good anti-snagging ability but also fully preserves the inherent moisture permeability, air permeability, and moisture wicking function of the microporous polyester.

[0080] Based on Examples 1-3 and Comparative Example 2, and referring to Table 2, it can be seen that when the drying and cooling rate is too fast and the final cooling temperature is too high in step S2, the placer molecules cannot be fully and orderly arranged in the amorphous region of the polyester fiber, making it difficult to form uniformly distributed nanoscale eutectic embedding points. This results in insufficient number and uneven distribution of micro-pits left on the fiber surface after sublimation, and the molecular chain segments of the anti-snagging film cannot be effectively filled to form a mechanical anchoring structure. Therefore, after multiple household washes, the anti-snagging level of Comparative Example 2 decreased, while the examples, through a controlled slow cooling process, pre-set sufficient eutectic templates, enabling the film to complete in-situ anchoring during the pore release stage. The anti-snagging level remained stable before and after washing, and the wash resistance and durability were significantly enhanced.

[0081] Based on Examples 1-3 and Comparative Example 3, and in conjunction with Tables 1 and 2, it can be seen that when the concentration of the film-forming polymer in step S3 is lower than the protection range of this application, the finishing solution cannot form a uniform and continuous dense anti-snagging film on the fiber surface. The film's mechanical strength is insufficient, and the initial anti-snagging level is already at a low level. In subsequent washing and friction tests, this thin film is more prone to damage and peeling, leading to a further decrease in the anti-snagging level after washing, and poor dry and wet friction integrity. The examples control the concentration of the film-forming polymer within a reasonable range and combine it with a crosslinking agent to form a three-dimensional network structure, giving the film excellent continuity, flexibility, and cohesive strength, providing durable and reliable anti-snagging protection for the fabric.

[0082] As can be seen from Examples 1-3 and Comparative Example 4, and from Tables 1 and 2, when the curing temperature in step S4 exceeds the protection range of this application, the excessively high temperature can allow the crosslinking reaction to proceed fully, but at the same time, it will cause thermal damage to the microporous structure of the polyester fiber and the formed anti-snagging film, resulting in partial micropore collapse of the fiber, film embrittlement, and a certain degree of attenuation of air permeability and wicking height. The examples control the curing temperature within the safe range under the protection of the placer, which ensures that the crosslinking agent is fully unsealed and completes the crosslinking reaction, while avoiding thermal damage to the microporous matrix and polymer film, so that the density, mechanical strength and fabric function retention of the anti-snagging film are balanced.

[0083] Based on Examples 1-3 and Comparative Example 5, and referring to Table 2, it can be seen that when the treatment time of the gaseous silane coupling agent in step S5 is too short, the gaseous silane molecules cannot fully diffuse to the entire interface area between the placer crystal and the anti-snagging film, resulting in incomplete coverage of the sacrificial release layer and local direct contact at the interface. During the subsequent sublimation process, the direct friction between the placer crystal and the inner wall of the film will cause micro-tears and interface weakening of the film layer. These micro-defects develop into macro-damage in the water washing and abrasion resistance tests, causing a decline in both the anti-snagging grade and abrasion resistance integrity after water washing. The examples provide sufficient treatment time to ensure that the sacrificial release layer is completely constructed at the interface, and that the placer does not directly contact the film during sublimation and pore release, thus preserving the integrity and durability of the film.

[0084] Based on Examples 1-3 and Comparative Example 6, and referring to Tables 1 and 2, it can be seen that when the heating temperature in step S6 is lower than the sublimation temperature of the placer, the placer cannot fully sublimate and escape, leaving a large amount of residue inside the micropores. This results in the micropores failing to recover effectively, and the fabric's moisture permeability, air permeability, and wicking height are severely suppressed, leading to poor functional retention. Simultaneously, because the placer is not completely removed, the pre-set eutectic embedding points on the fiber surface fail to transform into micro-pits, preventing the mechanical anchoring effect from being achieved, and resulting in insufficient bonding strength between the anti-snagging film and the fiber matrix. In this example, the heating temperature is set above the placer sublimation temperature, ensuring that the placer is completely converted into the gas phase and completely escapes, allowing for complete recovery of the microporous structure. Simultaneously, the micro-pit anchoring structure is formed, achieving a balance between anti-snagging durability and functional retention.

[0085] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A method for anti-snagging finishing of microporous polyester fiber fabric, characterized in that, Includes the following steps: S1. The microporous polyester fiber fabric is immersed in a solution containing a sublimable organic small molecule spacer to obtain the impregnated fabric. S2. Dry the impregnated fabric to allow the solvent to evaporate and the placer to crystallize and precipitate in the micropores, thereby obtaining a placer filling fabric. S3. The filling fabric is impregnated with a finishing liquid containing a film-forming polymer and a crosslinking agent to obtain a fabric coated with the finishing liquid. S4. The fabric coated with finishing liquid is dried and cured to form an anti-snagging polymer film on the outer surface of the fibers, thus obtaining a film-forming fabric. S5. The film-forming fabric is exposed to the vapor of a gaseous silane coupling agent for treatment, and a sacrificial layer is generated in situ at the interface between the placer and the anti-snagging film to obtain an interface-modified fabric. S6. The interface-modified fabric is subjected to heat treatment to sublimate the placer and allow it to escape from the micropores, thereby obtaining a pore-releasing fabric. S7. Cool the porous fabric to obtain a microporous polyester fiber fabric with anti-snagging finishing.

2. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S1, the sublimable organic small molecule occupier is selected from at least one of menthol, camphor, naphthalene, or benzophenone alkyl-substituted derivatives.

3. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 2, characterized in that, The alkyl-substituted derivative of benzophenone is 4-methylbenzophenone or 4,4'-dimethylbenzophenone.

4. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S1, the solution is an ethanol solution of a spacer, and the mass concentration of the spacer is 5% to 30%.

5. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S2, the drying process includes: first removing the solvent at 40~60°C, and then cooling to -5~10°C at a cooling rate of 0.5~5°C / min, so that the placer forms nanoscale eutectic embedding points on the surface of the amorphous region of the polyester fiber.

6. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S3, the film-forming polymer is an aqueous polyurethane or polyacrylate, and the crosslinking agent is a blocked isocyanate crosslinking agent; the concentration of the film-forming polymer in the finishing solution is 20-80 g / L, and the amount of crosslinking agent is 2%-8% of the mass of the film-forming polymer.

7. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S4, the drying temperature is 60~90℃ and the time is 2~10min; the curing temperature is 120~150℃ and the time is 1~5min.

8. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S5, the gas-phase silane coupling agent is hexamethyldisilazane or trimethylchlorosilane, the treatment temperature is 25~60℃, and the treatment time is 10~40min.

9. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, In step S6, the heating treatment temperature is 80~105℃ and the time is 15~60min.

10. The anti-snagging finishing method for microporous polyester fiber fabric according to claim 1, characterized in that, Step S6 also includes condensing and recovering the sublimated spacer vapor to obtain a recovered spacer, which is then reused to prepare the solution from step S1.